Stability enhancing of perovskite LaCoO3 by compositing with oxygen doped MoS2 in Fenton-like reactions. (June 2023) - Ma, Yansong; Ma, Biao; Wu, Di; Wang, Jun; Li, Yang; Fan, Xiaobin; Xia, Qing; Zhang, Fengbao; Peng, Wenchao
Abstract: Perovskite materials are reported to be effective in peroxymonosulfate (PMS) based Fenton-like reactions, the leaching rates of chalcogenide materials in perovskite materials are however serious, thus leading to bad performance in long-term stability. In this study, an O-doped MoS2 is synthesized to composite with LaCoO3, and the high catalytic activity of LaCoO3 is well preserved with greatly decreased Co leaching. During the BPA degradation with PMS as oxidant, ∼100% degradation can be achieved in 20 min and this degradation efficiency can be maintained for ∼45 h in a simulated fixed bed reactor, which is almost 3 times longer than the pure LaCoO3 . With the compositing of O-doped MoS2, the leached Co was greatly decreased and the dominated reactive oxidation species (ROS) transformed from SO4 – into O2 – with longer lifespan, thus resulting in the better stability. This study could promote the application of perovskite materials in the real industrial wastewater treatment. Graphical abstract: Image 1 Highlights: O-doped MoS2 is obtained only by the addition of more sulfur source. The O-doped MoS2 is compounded with LaCoO3 by an ultrasonicated mixing method. The long-term stability of LaCoO3 is improved by compositing with O-doped MoS2 . The dominated radicals change from SO4 . – into O2 – after introduction of MoS2 .